Diagnostic utility of diagnostic investigations to identify neuropathic pain in low back-related leg pain: protocol for a systematic review - Alison B Rushton; Nicola R Heneghan; Tim Noblet; David M Walton; Jai Mistry; Benjamin Bowling (BMJ Open)
Introduction Neuropathic pain in low back-related leg pain has gained increasing interest in contemporary research. Identification of neuropathic pain in low back-related leg pain is essential to inform precision management. Diagnostic investigations are commonly used to identify neuropathic pain in low back-related leg pain; yet the diagnostic utility of these investigations is unknown. This systematic review aims to investigate the diagnostic utility of diagnostic investigations to identify neuropathic pain in low back-related leg pain.Methods and analysis This protocol has been designed and reported in accordance with the Cochrane Handbook for Diagnostic Test Accuracy studies, Centre for Reviews and Dissemination and the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols checklist, respectively. The search strategy will involve two independent reviewers searching electronic databases (CINAHL, EMBASE, MEDLINE, Web of Science, Cochrane Library, AMED, Pedro), key journals (Spine, The Clinical Journal of Pain, PAIN, European Journal of Pain, The Journal of Pain, Musculoskeletal Science and Practice) and grey literature (British National Bibliography for report literature, OpenGrey, EThOS) from inception to 31 July 2023 to identify studies. Studies evaluating the diagnostic accuracy of diagnostic investigation to identify neuropathic pain in patients with low back-related leg pain will be eligible, studies not written in English will be excluded. The reviewers will extract the data from included studies, assess risk of bias (Quality Assessment of Diagnostic Accuracy Studies 2) and determine confidence in findings (Grading of Recommendations, Assessment, Development and Evaluation guidelines). Methodological heterogeneity will be assessed to determine if a meta-analysis is possible. If pooling of data is not possible then a narrative synthesis will be done.Ethics and dissemination Ethical approval is not required. Findings will be published in a peer-reviewed journal, presented at relevant conferences and shared with the Patient Partner Advisor Group at Western University, Canada.PROSPERO registration number CRD42023438222.